Pemberdayaan Masyarakat melalui Program Bantuan Sembako di Kelurahan Kampung Anggrung - Muhammad Muhammad; Aries DC Silaban; Yunita Yunita; Aqila Azura; Benjamin Sembiring Benjamin Sembiring (Joska: Jurnal Isori Kampar, 2024)
The basic food assistance program is one of the efforts to improve community food security, especially for vulnerable groups. This article discusses the implementation of the basic food assistance program in Kelurahan KAMPUNG ANGGRUNG, which aims to help residents affected by the COVID-19 pandemic and the economic crisis. The methods used in this community service include needs surveys, food distribution, and program impact evaluation. The results show that the program successfully helped 200 families for three months, with a significant increase in food access and a decrease in the level of food insecurity. In conclusion, the basic food assistance program proved effective in the short term, but needs to be integrated with long-term economic empowerment programs to achieve sustainable food security.